INFORMATION FILTERS IN AL-QUR'AN PERSPECTIVE: THE IDENTITY OF INDONESIAN MOSLEMS IN THE INFORMATION ERA - Erwin Rismanto; Khairunnisa Etika Sari (Jurnal Adabiyah: Humanities and Islamic Studies, 2018)
Since globalization era has gone around the world, every one is able to accept news easily. Many kinds of information can be seen and heard whenever they want. Society observes bad or good information, hence they can learn anything in one side, but in the other side the information attacks them. The broken society arises soon every where. And Moslems are parts of them. If the moslems do not understand how Al-Qur’an overcomes this problem, they will not improve theirself and will be vanished by the end of the time. So,they should learn about how Alqur'an guides in responding information.